2022
DOI: 10.1002/adhm.202200075
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Stimulation of Peripheral Nerves using Temporally‐Interfering Electrical Fields

Abstract: Electrical stimulation of peripheral nerves is a cornerstone of bioelectronic medicine. Effective ways to accomplish peripheral nerve stimulation (PNS) noninvasively without surgically implanted devices are enabling for fundamental research and clinical translation. Here, it is demonstrated how relatively high-frequency sine-wave carriers (3 kHz) emitted by two pairs of cutaneous electrodes can temporally interfere at deep peripheral nerve targets. The effective stimulation frequency is equal to the offset fre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 38 publications
0
24
0
Order By: Relevance
“…The method simultaneously applies two high frequency electric fields -too high to activate neurons individually -with slightly differing frequencies, thus allowing the fields to constructively and destructively interfere in time, resulting in an amplitude-modulated field. Neurons have been shown by us and by others to respond to the amplitude modulated field [8][9][10] . As a result, it is possible to restrict neurostimulation to the region where the two fields overlap.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…The method simultaneously applies two high frequency electric fields -too high to activate neurons individually -with slightly differing frequencies, thus allowing the fields to constructively and destructively interfere in time, resulting in an amplitude-modulated field. Neurons have been shown by us and by others to respond to the amplitude modulated field [8][9][10] . As a result, it is possible to restrict neurostimulation to the region where the two fields overlap.…”
Section: Introductionmentioning
confidence: 93%
“…The restriction of the stimulated region to that overlap region is the main advantage of TI, as careful electrode placement strategies provide the ability to stimulate deep brain targets without activating overlaying regions of tissue. Using simple TI with two pairs of electrodes on the scalp we demonstrated the ability to adequately activate deep targets, such as the hippocampus 9 , and to activate deep peripheral nerves, such as the sciatic and hypoglossal nerve 10,11 . However, it would be desirable to improve the focality sufficiently to target smaller brain and nerve structurese.g., an individual nucleus of the basal ganglia.…”
Section: Introductionmentioning
confidence: 99%
“…Here they showed the potential application of TI electrical stimulation for respiratory stimulation, further extending the clinical application of this novel approach. Botzanowski's study tested TI electrical stimulation on the murine sciatic nerve model, and then observed obvious muscle contractions and leg movements in mice corresponding to the envelope waveforms, validating the activation of the sciatic nerve (Botzanowski et al, 2022). Additionally, TI electrical stimulation could provide more effective actuation with lower current amplitudes than normal transcutaneous electrical stimulation (TENS).…”
Section: Clinical Applicationsmentioning
confidence: 96%
“…In addition to the regulating effects on the motor cortex in healthy subjects, TI electrical stimulation was also used to map out and stimulate pathological targets for locating epileptogenic zones and peripheral nerve stimulation (Collavini et al, 2021;Botzanowski et al, 2022).…”
Section: Clinical Applicationsmentioning
confidence: 99%
“…Peripheral Nerve Stimulation: The peripheral nerve stimulation (PNS) approach includes the combination of peripheral nerve stimulation by implantation electrodes or non-invasive stimulation of peripheral nerves by ultrasound [74] or electrical fields. [75] The PNS has been used as a means of orthodromic stimulation of non-nociceptive A𝛽 nerve fibers, which are mediated by A𝛽 fibers and relieve pain by feeling abnormal. [76] These fibers' activation causes the corresponding dorsal horn interneurons to fire, which in turn processes and transmits nociceptive information via peripheral A𝛽 and C nerve fibers.…”
Section: Input-type Bcismentioning
confidence: 99%